News Briefs. (April 2016) - Unknown
Abstract : Brown‐Forman awards $1 million for Speed Art Museum. GlaxoSmithKline awards $1 million under Healthcare Innovation Awards. Wells Fargo awards $7 million for microloan program. Microsoft employees raise record $125 million in 2015. JPMorgan Chase awards $2 million to address racial wealth disparities. Bechtel to continue signature partnerships with STEM education partners. Salesforce pledges $5 million to fight AIDS. Deutsche Bank Americas Foundation awards $250, 000 for career training initiative.